Energetic and environmental evaluation of microalgae biomass fermentation for biohydrogen production - Ferreira, Ana F. (2011)
This paper presents an energetic and environmental evaluation of the fermentative hydrogen production from the sugars of Scenedesmus obliquus biomass hydrolysate by Clostridium butyricum. The main purpose of this work was to evaluate the potential of H2 production and respective energy consumptions and CO2 emissions in the global fermentation process: hydrolysis of S. obliquus biomass, preparation of the fermentation medium, degasification and incubation. The scale-up to industrial production was not envisaged. Energy consumption and CO2 emissions estimations were based on SimaPro 7.1 software for the preparation of the fermentation medium and the use of degasification gas, nitrogen. The functional unit of energy consumption and CO2 emissions was defined as MJ and grams per 1 MJ of H2 produced, respectively. The electricity consumed in all hydrogen processes was assumed to be generated from the Portuguese electricity production mix. The hydrogen yield obtained in this work was 2.9 ± 0.3 mol H2/mol sugars in S. obliquus hydrolysate. Results show that this process of biological production of hydrogen consumed 281-405 MJ/MJH2 of energy and emitted 24-29 kgCO2/ MJH2. The fermentation stages with the highest values of energy consumption and CO2 emissions were identified for future energetic and environmental process optimisation.